2009
DOI: 10.5650/jos.58.355
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Alpha-Linolenic Acid Inhibits Angiotensin-Converting Enzyme Activity and mRNA Expression Levels in the Aorta of Spontaneously Hypertensive Rats

Abstract: Several studies have shown that dietary alpha-linolenic acid (ALA) is associated with a reduced risk of cardiovascular disease and has an antihypertensive effect. Blood pressure is regulated mainly by angiotensin-converting enzyme (ACE). In the present study, we investigated the effect of dietary ALA on ACE to clarify the mechanism of the antihypertensive effect in spontaneously hypertensive rats (SHR). Sixweek-old SHR were fed a diet containing either 10% ALA-rich flaxseed oil or high oleic safflower oil as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
(40 reference statements)
2
19
0
1
Order By: Relevance
“…The results showed that 30% fructose solution administered for 30 d promoted an increase in SBP and glucose and triglyceride levels and reduce HDL cholesterol levels, demonstrating that this is an effective model for MS induction in Wistar rats. In addition, both FO and SDG partially prevented these changes, in agreement with the findings of previous studies (Ogawa and others ; Tzang and others ; Park and Velasquez ).…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that 30% fructose solution administered for 30 d promoted an increase in SBP and glucose and triglyceride levels and reduce HDL cholesterol levels, demonstrating that this is an effective model for MS induction in Wistar rats. In addition, both FO and SDG partially prevented these changes, in agreement with the findings of previous studies (Ogawa and others ; Tzang and others ; Park and Velasquez ).…”
Section: Discussionsupporting
confidence: 92%
“…The Ang 1, 7 opposes the vasoconstrictor actions of Ang-II and induces vasorelaxation. 61 The ω-3 PUFAs reduce ACE-2 activity; 6264 and ACE-2 mRNA has been reported to be down-regulated in the aorta of the spontaneously hypertensive rats fed a diet rich in ALA. 65 Last, the strong correlation between the up-regulation of Ace-2 and the tissue levels of the EpDPEs and EpETEs and plasma levels of Ang-II suggests that these epoxides might modulate Ace-2 and thus contribute to the regulation of blood pressure.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, compared to flaxseed and perilla oils, P. volubilis seed oil have high α-linolenic acid content, which is converted to eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in living organisms (Kayama, 1995;Wada, 2008). The oil is thought to have anti-inflammatory properties and offers protection against blood clots, coronary heart disease and high blood pressure (Sawai, 2009;Williams, 2011;Okuyama, 2001;Ogawa et al, 2009;Albelt et al, 2005;Hu et al, 1999). Individuals who either cannot or do not eat fish on a daily basis, or who only eat fish infrequently, can supplement their n-3 fatty acid intake with flaxseed oil or perilla oil (Editorial Department, 2005, i).…”
Section: Introductionmentioning
confidence: 99%